Allometric equations for predicting the aboveground biomass of square bamboo, Chimonobambusa quadrangularis. Issue 6 (2nd November 2019) - Inoue, Akio; Koshikawa, Kazuki; Sato, Motohiro; Shima, Hiroyuki
ABSTRACT: Allometric equations for predicting the aboveground biomass of square bamboo, Chimonobambusa quadrangularis (Franceschi) Makino, were developed. To this end, 20 samples of C. quadrangularis were harvested, and the aboveground biomass of the culm and that of the branches and leaves were measured. The whole aboveground biomass of C. quadrangularis ranged from 128 g to 2, 075 g, with the average of 910 g. The results showed that the culm diameter at breast height ( D ) was a better practical predictor of aboveground biomass than other culm attributes such as total culm length ( H ) and D 2 H . The allometric power exponent between biomass and D was larger in the culm (2.258) than in branches and leaves (1.262). The aboveground biomass partitioning to the culm increased from 46% to 75% with increasing D, which was lower than that of other bamboo species. This implies that the branches and leaves should be the indispensable components when quantifying the aboveground biomass of C. quadrangularis . The allometric equations presented here will be useful and beneficial when establishing the sustainable management strategy as well as evaluating the site productivity of C. quadrangularis stands.